An evaluation of brachial plexus block using a nerve stimulator versus ultrasound guidance: A randomized controlled trial - Shivinder Singh; Rakhee Goyal; Kishan Kumar Upadhyay; Navdeep Sethi; Ram Murti Sharma; Anoop Sharma (Wolters Kluwer Medknow Publications, 2015)
Background and Aims: This study was carried out to evaluate the difference in efficacy, safety, and complications of performing brachial plexus nerve blocks by using a nerve locator when compared to ultrasound (US) guidance. Material and Methods: A total of 102 patients undergoing upper limb surgery under supraclavicular brachial plexus blocks were randomly divided into two groups, one with US and the other with nerve stimulator (NS). In Group US, "Titan" Portable US Machine, Sonosite, Inc. Kensington, UK with a 9.0 MHz probe was used to visualize the brachial plexus and 40 ml of 0.25% bupivacaine solution was deposited around the brachial plexus in a graded manner. In Group (NS), the needle was inserted 1-1.5 cm above mid-point of clavicle. Once hand or wrist motion was detected at a current intensity of less than 0.4 mA 40 ml of 0.25% bupivacaine was administered. Onset of sensory and motor block of radial, ulnar and median nerves was recorded at 5-min intervals for 30-min. Block execution time, duration of block (time to first analgesic), inadvertent vascular puncture, and neurological complications were taken as the secondary outcome variables. Results: About 90% patients in US group and 73.1% in NS group, had successful blocks P = 0.028. The onset of block was faster in the Group US as compared to Group NS and this difference was significant (P 0.007) only in the radial nerve territory. The mean duration of the block was longer in Group US, 286.22 ± 42.339 compared to 204.37 ± 28.54-min in Group NS (P < 0.05). Accidental vascular punctures occurred in 7 patients in the NS group and only 1 patient in the US group. Conclusion: Ultrasound guidance for supraclavicular brachial plexus blockade provides a block that is faster in onset, has a better quality and lasts longer when compared with an equal dose delivered by conventional means.